PERAN CITRA MEREK MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP BOOKING INTENTION PADA CHAIN HOTEL DI BALI - Putu Laksmita Dewi Rahmayanti; I Wayan Suartina; I Komang Sumerta (Forum Manajemen, 2022)
The economy in Bali relies on tourism sector, but due to the Covid-19 outbreak, regional income in Bali decreased in 2020. The tourism accommodation sector is one sort of business involved in the affected tourism industry. Bali has a large number of hotels, particularly chain hotels such as Aston, Ibis, Harris, Fave, and Horizon Hotels. When compared to local hotels, the hotel chain has the strength of a strong brand because it is more well-known. However, hotel chains in Bali were also affected by the Covid-19 outbreak, as seen by the decreased occupancy rate. As a result, the researcher investigated the role of brand image in mediating the effect of social media marketing on chain hotel booking intentions in Bali. Data was gathered by having 70 domestic tourists fill out google form questionnaire. Purposive sampling was utilized as the sample technique. SMART-PLS 3.0 was used to analyze the data. The findings of this study show that social media marketing has a positive and significant effect on brand image, that social media marketing has a positive and significant effect on booking intention, that social media marketing has a positive and significant effect on booking intention, and that the brand image variable can mediate the influence of social media marketing on booking intention.